MENGKONSUMSI MINUMAN TEH BERSODA DAN TEH TIDAK BERSODA TERHADAP PH SALIVA - Irmanita Wiradona; Sadimin ,; Silvy Herlina Fitri (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2017)
TITLEEFFECT OF SODA AND NON SODA CONTAINED TEA TO ACIDITY (pH) OF SALIVAABSTRACTThe saliva pH is the acidity of saliva. Carbonated tea beverage is tea drink mixed with soda. Carbonated beverages are tea not drink tea without soda mixture. In carbonated tea beverages containing sugar, CO2 (carbondioxide), ascorbic acid and citric acid and the carbonated drink tea does not contain sugar. From the contain of both these drinks can affect the pH of saliva. The purpose of this study is to determine differences in the pH of saliva between carbonated tea drinks and tea drinks are not fizzy.This study is conducted by quasi-experiment with a design. Pretest-posttest study population as many as 212 students of Department of Dental Nursing taken 20% in order to get a sample of 42 people, the technique decision-purposive sampling. The data obtained is pH of saliva before and after drinking tea and tea carbonated ale. Analysis of the data used to see difference Saliva pH between tea and tea carbonated fizzy not done with the Mann-Whitney. The results showed that the differences in the average pH of saliva before and after tea sparkling is 0.9 and the average value of the difference before and after drinking tea are not sparkling is 0.4. The conclusion of this study is the change in no difference the pH Saliva between drinking carbonated tea and tea drinking ale in Dental Nursing student.